2016
DOI: 10.1021/acs.analchem.5b04286
|View full text |Cite
|
Sign up to set email alerts
|

Amyloid-β-Secondary Structure Distribution in Cerebrospinal Fluid and Blood Measured by an Immuno-Infrared-Sensor: A Biomarker Candidate for Alzheimer’s Disease

Abstract: The misfolding of the Amyloid-beta (Aβ) peptide into β-sheet enriched conformations was proposed as an early event in Alzheimer's Disease (AD). Here, the Aβ peptide secondary structure distribution in cerebrospinal fluid (CSF) and blood plasma of 141 patients was measured with an immuno-infrared-sensor. The sensor detected the amide I band, which reflects the overall secondary structure distribution of all Aβ peptides extracted from the body fluid. We observed a significant downshift of the amide I band freque… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
127
3
2

Year Published

2016
2016
2022
2022

Publication Types

Select...
7

Relationship

5
2

Authors

Journals

citations
Cited by 100 publications
(139 citation statements)
references
References 44 publications
7
127
3
2
Order By: Relevance
“…A slight increase of the intensity at the Amide I region (1,650-1,630 cm ; P = 0.1069, 95% CI = −0.005, 0.0005), observed in our AD patients, could presumably be caused by increased levels of Aβ plaques. In a recent study, using a more complex setting with a specialized, immuno-IR sensor, it was shown that the structural changes of Aβ peptide from α-helix to β-sheet, seen in AD, can be detectable by a significant downshift at the Amide I region (1,643 cm ), and this further proves the importance of this region (13). Similar results were seen in an another study, which analyzed protein solutions containing soluble and aggregated forms of tau protein (random coil and β-sheet, respectively); in this case, a transition from a maximum peak at 1,650 cm −1 to a peak at 1,630 cm −1 was evident (25).…”
Section: Discussionmentioning
confidence: 90%
See 2 more Smart Citations
“…A slight increase of the intensity at the Amide I region (1,650-1,630 cm ; P = 0.1069, 95% CI = −0.005, 0.0005), observed in our AD patients, could presumably be caused by increased levels of Aβ plaques. In a recent study, using a more complex setting with a specialized, immuno-IR sensor, it was shown that the structural changes of Aβ peptide from α-helix to β-sheet, seen in AD, can be detectable by a significant downshift at the Amide I region (1,643 cm ), and this further proves the importance of this region (13). Similar results were seen in an another study, which analyzed protein solutions containing soluble and aggregated forms of tau protein (random coil and β-sheet, respectively); in this case, a transition from a maximum peak at 1,650 cm −1 to a peak at 1,630 cm −1 was evident (25).…”
Section: Discussionmentioning
confidence: 90%
“…A major goal is the detection of AD at a very early stage, even before the patient becomes symptomatic (10,13). Early diagnosis is crucial, as once the patient appears with clinical symptoms, the damage that has occurred in the brain may already be irreversible.…”
Section: Significancementioning
confidence: 99%
See 1 more Smart Citation
“…Current biomarkers include neuroimaging and CSF neurochemical diagnosis (Aβ, Tau, and phosphorylated Tau) [11,12], but these diagnostic tools are not available in many primary care units. Cognitive testing is commonly used as a diagnostic tool, including the Clinical Dementia Rating (CDR), which classifies the severity of dementia [13,14].…”
Section: Introductionmentioning
confidence: 99%
“…Recently, we established a robust method to specifically immobilize his‐tagged and lipidated proteins on germanium IREs through binding to solid‐supported lipid bilayers9, 10 and to nitrilotriacetic acid (NTA) groups attached to planar surfaces as well as to dextran brushes based on self‐assembled monolayers (SAMs) of silanes or thiols 11, 12, 13, 14. This recent breakthrough allowed us to use ATR‐FTIR spectroscopy as a flow‐through‐based sensor of conformational change to examine the conformational effects of binding resorcinol scaffold inhibitors to the molecular chaperone heat‐shock protein 90 (HSP90).…”
mentioning
confidence: 99%